Exploring the co-benefits (and costs) of home gardening for biodiversity conservation. Issue 3 (4th March 2019) - Raymond, Christopher M.; Diduck, Alan P.; Buijs, Arjen; Boerchers, Morrissa; Moquin, Robert
ABSTRACT: Despite growing evidence pointing to the multiple benefits of home gardening, few studies have considered the health and well-being benefits perceived by gardeners who are principally motivated by biodiversity conservation (i.e. home gardening for biodiversity conservation). This study explores the environmental, social and economic co-benefits (and costs) of home gardening for biodiversity conservation in the City of Winnipeg, Canada. A total of 42 semi-structured interviews (30–60 min each) were conducted with 50 home gardeners who were formally certified or locally recognised for undertaking multiple gardening activities that promote biodiversity conservation. Thematic analysis revealed that study participants self-reported a range of environmental, psychological, physiological and social outcomes associated with their home gardening experiences. Despite home gardening often being a solitary activity, most gardeners valued the multiple forms of social interaction that occurred during important social events in their garden, or when connecting with passers-by. Home gardeners also cited benefits related to connection to nature and place attachment; attention restoration; reduced stress and anxiety; improved mood; satisfaction and pride; increased self-esteem and courage to do things differently in life; and, important education or learning opportunities. However, conflicts relating to the nexus between biodiversity and perceived tidiness of gardens emerged, which raise important ethical and social justice issues for sustainability planning. We compare key insights to the benefits (and costs) of community gardening and make some recommendations for future research, including how to engage more disadvantaged groups in gardening for conservation.